Development of methodological foundations for the development and implementation of the state policy of reindustrialization of regional systems - Aimagambetov, Ye.B.; Ignatyuk, A.I.; Amirova, G.N.; Borisova, Ye.I. (BUKETOV BUSINESS REVIEW, 2021)
Object: The purpose of the study is to substantiate methodological issues of state policy and modeling of the dynamic development of regional systems as an inseparable triad "ecology-society-economy" in the conditions of various stages of reindustrialization. Methods: methods of system analysis and economic synthesis of reindustrialization factors and assessment of their impact on the development of ecological and socio-economic systems are used, which will increase the effectiveness of state policy and management decisions in the field of scientific, technical, industrial and environmental policies. Results: The developed methodology for assessing the state and dynamics of the development of ecological and socio-economic systems is a tool for further, more in-depth analysis of the development problems of the countries that are part of the EAEU zone, in solving which it is impossible to do without the use of methods of state regulation of the economy. It is established that socio-economic policy and the organizational, economic, and managerial mechanisms by which it is implemented have a significant impact on development. In this regard, it is important not only to determine the degree of efficiency of the use of available resources, but also to what extent and how to make up for their lack. The presence or absence of effective policies is reflected in the reduction or growth of barriers to development. Conclusions: Recommendations on the choice of reindustrialization options are as follows: - systematic consideration of three interrelated elements: realization of industrial potential, effective use of labor resources, ensuring normal working conditions and effective employment of the population; advanced development of infrastructure; - consideration of environmental effects directly related to the process of re-industrialization;  a retrospective study of the industrial development of the territory is the most important source of information for the development of directions for the allocation of productive forces; - decision-making is based on taking into account social, economic, natural and technological criteria indicators, which provide for compliance with the principle of coordinating the interests of the subjects of reindustrialization, taking into account social priorities.